High thermal stability Cu2O@OZrP micro-nano hybrids for melt-spun excellent antibacterial activity polyester fibers. (10th August 2021) - Zhou, Jialiang; Wang, Yaping; Pan, Weinan; Xiang, Hengxue; Li, Peng; Zhou, Zhe; Zhu, Meifang
Abstract: Public safety incidents caused by bacterial infections have attracted widespread attention towards antibacterial textiles (fibers, fabrics, etc.). Nevertheless, it is still challenging to efficiently load inorganic nano-antibacterial materials in polymer fibers. In this work, zirconium phosphate (ZrP, layered micro-nano materials) was utilized as a micro-nano carrier. The octadecyl triphenyl phosphonium bromide (OTP) was intercalated between the ZrP sheets by the ion exchange method to improve the carrier-polymer compatibility and the antibacterial performance. Through in-situ chemical reduction, the ultra-small nano-sized cuprous oxide (Cu2 O < 5 nm) was loaded on the outer surface of ZrP to realize the uniform and stable dispersion of the Cu2 O on the carrier and improve the antibacterial performance. The ZrP nanosheets loaded with Cu2 O and OTP (Cu2 O@OZrP) had excellent antibacterial properties, and the antibacterial rate against E. coli, S. aureus and C. albicans was more than 99 %. The intercalation amount of OTP in Cu2 O@OZrP can reach 16 %, and the thermal stability was excellent and a significant increase in the Zeta potential. Indeed, the decomposition temperature was greater than 350 °C, which was suitable for high-temperature melt processing of polymers. Consequently, we prepared PET/Cu2 O@OZrP fibers using polyethylene glycol terephthalate (PET), which accounts for 70 % of the total chemical fibers, as the fiber matrix. PET/Cu2 O@OZrP fibers exhibited excellent mechanical property and antibacterial performance when the content of Cu2 O@OZrP was only 0.2 %. The antibacterial rate against five types of bacteria including super bacteria ( MRSA, VRE ) was more than 99 %.